'External conditions affecting a harmonious family': Lessons learned from a school-based parent education programme in Hong Kong. (April 2013) - Luk-Fong, Pattie Yuk Yee
This article documents a parent education presentation on 'External conditions affecting a harmonious family' within a school-based parent education programme in Hong Kong. The presentation adopted an eco-systems approach for understanding families and argued for the need to include the external conditions for a harmonious family as an important element for a school-based parent education programme. External conditions affecting a family included the impact of globalization on the family, such as: (1) Consumerism on parenting and conceptions of marriage; (2) neo-capitalism creating new issues of family-work balance; and (3) outsourcing of family functions. Parents' feedback to these concepts is discussed, and a conceptual framework of a healthy family is proposed. Implications for school counselling professionals and family practitioners are also discussed.